The Uniqueness Of Prosocial Behavior In Bali On The Village Fund Management Accountability - Made Gede WIRAKUSUMA; Putu Gede Wisnu Permana KAWISANA (Indonesia Strategic Sustainability, 2022)
This research is based on the phenomenon of accountability of village funds that are still needed to strengthen the Indonesian government's policies of the rural and urban sector in developing the nation and state. The research respondents were village government officials in Tabanan Regency, as a district with the largest number of villages, with village funds also, in Bali Province in 2019. The survey used a questionnaire, distributed to village government officials that were clustered (cluster random sampling) based on 10 sub-districts with 133 villages in Tabanan Regency. There are 3 positions of village government officials (village head or village secretary, and head of financial affairs) as respondents, and a sample of 72 questionnaires was obtained, according to the cluster and proportion of the number of villages per sub-district. The results of testing with Moderated Regression Analysis show that pro-social behavior strengthens the influence of human resource competencies, as well as the leadership of village government officials, in relation to increasing accountability of village fund management. Meanwhile, pro-social behavior has not proven its influence in the relationship between community participation and village fund management accountability.